Błąd pełnomocnika, prokuratora i pracownika sekretariatu jako niemożność przywrócenia terminu zawitego w procedurze karnej a standardy konstytucyjne - Kolendowska-Matejczuk, Marta (PRAWO i WIĘŹ, 2025)
The paper discusses issues related to the interpretation of the premise of „reasons beyond the control of a party” contained in Article 126 § 1 of the Code of Criminal Procedure, which regulates the institution of the reinstated time limit in the context of criminal procedure. The analysis of the interpretation of the above-mentioned provision was confronted with constitutional standards, and the conclusions developed in this publication indicate the inconsistency of Art. 126 § 1 of the Code of Criminal Procedure with the Constitution and postulate its pro-constitutional interpretation.